Penggolongan Mangga cv Arumanis Berdasarkan Mutu Internal - Yunisa Tri Suci; I Wayan Budiastra; Y. Aris Purwanto (PERTETA, 2015)
The purpose of this study was to assess NIRS method to classify mango cv Arumanis based on its internal quality during cold storage. Reflectances of mango at harvest date (H0), 12 days of storage (H12), and 22 days of storage were measured by using NIRflex Spectrometer at wavelengths of 1000-2500 nm, followed by measurement of physico chemical properties of mango (total soluble solid, total acid, TSS-acid ratio, firmness and weight loss). Unsupervised Principal component analysis (PCA) and pre treatment NIR spectra were performed on NIR spectra to classify mango (H0, H12, H22) and mahalanobis distance was used to validate the results. The result showed that reflectances of mango decreased during storage indicating the increase of NIR absorption by internal compounds of mango. TSS, TSS-acid ratio, and weight loss increased during storage as total acid and firmness decreased. NIRS and PCA analysis with pretreatment of quantile normalization and smoothing, and mahalanobis distance parameter could classify mango of 0, 12 and 22 days of storage based on its internal quality with accuracy of 87 %.